Nomenclatural notes relevant to the flora of Indonesia. - Ian Turner (Research Center for Biology, 2012)
Some species described by Teijsmann and Binnendijk were published slightly earlier than is sometimes believed because of duplicate publication in different journals. In a few cases this results in a change in priority between competing names. The case of Rothmannia schoemannii (Rubiaceae) having priority over R. exaltata is highlighted. Zollinger published a number of new combinations in Annonaceae a few months before Miquel, so a trio of accepted names, Mitrephora polypyrena, Orophea celebica and O. corymbosa, should be correctly attributed to him.